Risky behaviours among university students in Italy - Andrea Poscia; Paolo Parente; Emanuela Maria Frisicale; Adele Anna Teleman; Chiara de Waure; Maria Luisa Di Pietro (Istituto Superiore di Sanità, 2015)
BACKGROUND: The use of psychoactive substances is one of the most important public health issues. Tobacco, alcohol and illicit drugs are among the top risk factors for ill-health defined by World Health Organisation. The risky behaviours acquired in teenage can be magnified or decreased during university when a person starts having more awareness about the importance of own wellness. This paper describes the results of the project "Sportello Salute Giovani" ("Youth Health Information Desk") with respect to risky behaviours in a large sample of Italian university students. MATERIALS AND METHODS: 18 questions of the survey "Sportello Salute Giovani" dealing with risky behaviors, the use of psychoactive substances such as tobacco, alcohol and illicit drugs were included. Absolute and relative frequencies were calculated. Besides, chi square test were used to test the differences in sex, age class and socio-economic status. RESULTS: About 24% of the interviewed students currently smokes. 89% and 42.2% respectively drinks at least rarely or weekly beer, wine or spirits. About 40% of students smoked at least a joint and about 2% used other drugs (mostly cocaine). CONCLUSION: The "Sportello Salute Giovani" survey suggests that the frequency of risky behaviours in Italian university students is not reassuring, although they should be aware about the negative consequences on their and others health because of their educational level.